2018
DOI: 10.21037/jtd.2018.11.09
|View full text |Cite
|
Sign up to set email alerts
|

Age-stratified sex differences in polysomnographic findings and pharyngeal morphology among children with obstructive sleep apnea

Abstract: Background: Childhood obstructive sleep apnea (OSA) has important implications for growth, learning, behavior, cognition and cardiovascular health as well as snoring and OSA in adulthood. In this study, we elucidated the sex differences in polysomnographic (PSG) findings and pharyngeal radiographic data in pediatric OSA patients. Methods: Sixty three children (age between 3 and 15 years old) with OSA [defined as apnea-hypopnea index (AHI) ≥1/h by polysomnography] were enrolled. Lateral neck radiographs were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…Tonsil hypertrophy was significantly increased the risk of OSA by 3.5 times. 27 Other study has shown that there is a significant correlation between adeno-tonsillar hypertrophy and OSA in pre-adolescents than in adolescents. Our results were in agreement with the statement that the upper respiratory tract area and the adenoidal-nasopharyngeal (A/N) ratio were not significantly different in the pre-adolescent group.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Tonsil hypertrophy was significantly increased the risk of OSA by 3.5 times. 27 Other study has shown that there is a significant correlation between adeno-tonsillar hypertrophy and OSA in pre-adolescents than in adolescents. Our results were in agreement with the statement that the upper respiratory tract area and the adenoidal-nasopharyngeal (A/N) ratio were not significantly different in the pre-adolescent group.…”
Section: Discussionmentioning
confidence: 92%
“…Hence, the operative treatment for children with OSA is primarily tonsillectomy, sometimes accompanied by adenoidectomy. 27 Oxygen free radicals released from asthmatics' airways regulate 5-lipoxygenase activity in pharyngeal lymphoid tissue, triggering the synthesis of cysteinyl leukotriene, causing tonsilloadenoid hypertrophy. 8 Tonsil hypertrophy is one of the pathological links between intermittent upper airway obstruction during sleep and repeated episodes of lower airway obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be possibly attributed to the small sample as well as the onset of OSAS in childhood. Gender differences in the prevalence of OSAS occur from adolescence and henceforth, due to mainly anatomical differentiations in the UA 39 , whereas during childhood, boys and girls demonstrate similar OSAS severity, indicating different pathophysiology 40 . In fact, adenotonsillar hypertrophy is the main cause of OSAS in prepubertal children, regardless of the gender 41 .…”
Section: Discussionmentioning
confidence: 99%
“…It could be explained by hormonal changes due to puberty, because OSA is more prevalent in male adults. 49 50 Since our study group was limited to 13-year-old patients, they probably were not under hormonal effects yet.…”
Section: Discussionmentioning
confidence: 99%